Предмет: Алгебра,
автор: Lizattitb
поможить пожалуста!!!!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
1
Ответ: (x-1) · (x² - 7x + 1)
Объяснение:
Если разложить на множители, то
x³ - 8x² + 8x - 1 = (x³ - 1) - (8x² - 8x) = (x-1)(x²+x+1) - 8x(x-1) =
= (x-1) · (x² + x + 1 - 8x) = (x-1) · (x² - 7x + 1)
Похожие вопросы
Предмет: Математика,
автор: alookashama
Предмет: Алгебра,
автор: Аноним
Предмет: Биология,
автор: natazyaazet
Предмет: Математика,
автор: Oxxxymoron1
Предмет: Математика,
автор: Матеша111